Improving Students’ Vocabulary Mastery through Word Wall Method at Ninth Graders of SMPN 1 Mamuju - Syahban Mada Ali (Universitas Muhammadiyah Enrekang, 2019)
This research was a classroom action research (CAR). The objective of this research was to find out students’ vocabulary mastery especially its application in a correct sentence pattern by using Word Wall method to the ninth grade students of SMP Negeri 1 Mamuju. This research consisted of three cycles. There were 30 students in one class that followed this research. The result showed there was improvement of the students’ vocabulary. It could be seen on their average score in the first cycle improved by 49.25%, from the diagnostic test 34.83%. Then, it improved more in the second cycle by 60.8% and more in the third cycle that achieves 68.25%. However, despite getting the students’ average score improved, after applying the three cycles, it is still not success achieving the Minimum Completeness Criteria (MCC) of the subject that was 75.